Opera poetică a lui Grigore Vieru în circuit valoric ucrainean - Dumitru APETRI (Philologia)
In this article is shown the process of reception of Grigore Vieru’s poetic works that is produced in the cultural-literary area of Ukraine. It can be seen that, starting from 1969, the phenomenon unfolds in two ways. The first way – publishing a certain number of creations in the form of lyrics cards for preschoolers and schoolchildren and volumes for adults; the second – the inclusion of certain Vieru’s works, as a rule, in the form of cycles, in collections containing selected writings from Romanian literature, sometimes from other literatures as well. Considering the contents of the lyric cards and volumes, the author concludes that the Ukrainian publishing houses have made a successful selection of the works to be translated and that the personality of the poet is presented according to merit, that is, in high tones, whether in annotations, prefaces, afterwords or portrait sketches. Collective collections, which included certain works in their pages, made a considerable contribution to the promotion of Vieru’s poetic treasure, giving them access to various categories of readers.